The Effect of Content Marketing and Influencer Marketing on Purchasing Decisions for Azarine Sunscreen Products for Tiktok Gen Z Users in Surabaya - Nina Zenitha Sekar Sari; Siti Aminah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The demand for skincare products has an impact on the number of cosmetic companies that have increased, this has led to competition in the industry being very competitive. This study aims to determine the effect of content and influencer marketing on purchasing decisions for Azarine sunscreen products for TikTok Gen Z users in Surabaya. Research samples were distributed to Gen Z, who use TikTok and live in Surabaya, they purchased Azarine sunscreen products and saw influencer content related to Azarine sunscreen products. Sampling using the purposive sampling method, and the number of samples used was 105 respondents. Data analysis utilizes the SEM method using the PLS analysis tool. The results showed that content marketing and influencer marketing positively and significantly affected purchasing decisions for Azarine sunscreen products for TikTok Gen Z users in Surabaya.